Treatment of palm oil mill effluent using evaporation and adsorption techniques - Kathiravale, Sivapalan; Ripin, Adnan (1997)
The bench scale experiment was carried out with an aim to teat the palm oil mill effluent by utilizing it's physical and chemical characteristics. The raw effluent has a temperature of 80 degree C to 85 degree C, thus by introducing a vacuum of 350mm Hg, the effluent will evaporate without any addition of heat. The vapour produced was then passed through a bed of adsorbent. Four different types of adsorbents were studied in this part namely activated carbon, natural zeolite and synthetic zeolite of the X and A type. The vapour, (before adsorption) when analysed showed a 99% removal of most polluting parameters monitored except for pH, COD and BOD. The effluent was able to be concentrated to as high as 25% solid content from the initial content of 3-5% solids. This will result in a recovery of 80% of the water content and also the POME volume will reduce by the same percentage. The concentrated effluent analysis showed a high content of notrogen, phosphorus and pottasium which can be used as feed material for the making of fertiliser. Next, the adsorption process results indicated that the synthetic zeolite gave a better treatment than that of natural adsorbents.